The value of polymorphism RRO12ALA gene PPARG in violation of lipid peroxidation and antioxidant protection in patients with type 2 diabetes mellitus - Ziablytsev, S. V.; Mokrii, V. Y.; Crystal, M. V. (Journal of Education, Health and Sport, 2016)
Ziablytsev S. V., Mokrii V. Y., Crystal M. V. The value of polymorphism RRO12ALA gene PPARG in violation of lipid peroxidation and antioxidant protection in patients with type 2 diabetes mellitus. Journal of Education, Health and Sport. 2016;6(9):626-636. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.158861 http://ojs.ukw.edu.pl/index.php/johs/article/view/3888 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. The value of polymorphism Rro12Ala gene PPARG in violation of lipid peroxidation and antioxidant protection in patients with type 2 diabetes mellitus S. V. Ziablytsev, V. Y. Mokrii, M. V. Crystal Bogomolets national medical university Resume. The incidence of type 2 diabetes mellitus is increasing in Ukraine and worldwide. The severity of this disease is determined by the number of complications, which are based on lipid peroxidation (LPO). Today, the influence of gene polymorphisms Pro12Ala PPARG on oxidative and antioxidant processes is not in doubt. We studied the association between gene polymorphism Pro12Ala rs1801282 PPARG and intensification of lipid peroxidation and antioxidant systems (AOS) in 88 patients with type 2 diabetes, using analysis of variance. In the 12Pro allele carriers male found probable increased intensification of lipid peroxidation than in women, with increasing levels of DC (p=0,034) and MDA (p=0,001). Reducing the enzyme catalase level of AOC in patients with type 2 diabetes was observed in the case of genotype Pro12Pro gene PPARG on 21.7% compared with heterozygotes (F=8,17; p=0,005) and the presence of the allele 12Pro (F=6,28 , p=0,013). Found significantly higher activity of AOC in the form of increasing the level of α-TF (p=0,016) and catalase activity (p=0,034) among male patients with gene polymorphism Pro12Ala PPARG, than homozygotes for allele 12Pro. Key words: lipid peroxidation; antioxidant system; type 2 diabetes mellitus; polymorphism Pro12Ala rs1801282 of gene PPARG